Public Space Development Model After Large-Scale Slum Area Revitalization in Maros Regency: A Case Study of Allepolea and Maccini Baji Areas, Lau District - Muhammad Akshar; Muhammad Aryanugraha Ismajaya (Universitas Ichsan Sidenreng Rappang, 2025)
The arrangement of slum areas is one of the important strategies in realizing a livable, healthy, and sustainable residential environment. However, after the arrangement, there is often a vacancy in social functions in the area due to the suboptimal utilization of public spaces. This study aims to formulate a model for the development of inclusive and adaptive public spaces in large-scale post-slum arrangement areas, using case studies in the Allepolea and Maccini Baji areas, Lau District, Maros Regency, which have a total slum area of 17.23 hectares. The research method used is a qualitative-descriptive approach with data collection techniques including field observation, in-depth interviews, questionnaire surveys, and a review of planning documents (RTRW 2022–2042). The results show that there is an urgent need for public spaces that can accommodate social activities, informal economic activities, and interactions between residents. Based on the analysis, an alternative model for public spaces based on local needs is formulated, which includes functional, ecological, and socio-cultural aspects. This model is expected to serve as a reference for planning public spaces in residential areas that have been arranged, both in Maros and in other similar areas.